Post-traumatic peripheral vestibular disorders (excluding positional vertigo) in workers following head injury - Misale, Priyanka; Hassannia, Fatemeh; Dabiri, Sasan; Brandstaetter, Tom; Rutka, John (Scientific reports, 2021)
Benign paroxysmal positional vertigo has typically been reported to be the most common cause of post-traumatic dizziness. There is however paucity in the literature about other peripheral vestibular disorders post-head injury. This article provides an overview of other causes of non-positional dizziness post-head trauma from our large institutional experience. The UHN WSIB Neurotology database (n = 4291) between 1998 and 2018 was retrospectively studied for those head-injured workers presenting with non-positional peripheral vestibular disorders. All subjects had a detailed neurotological history and examination and vestibular testing including video nystagmography, video head impulse testing (or a magnetic scleral search coil study), vestibular-evoked myogenic potentials, and audiometry. Imaging studies included routine brain and high-resolution temporal bone CT scans and/or brain MRI. Based on a database of 4291 head-injured workers with dizziness, 244 were diagnosed with non-positional peripheral vertigo. Recurrent vestibulopathy (RV) was the most common cause of non-positional post-traumatic vertigo. The incidence of Meniere’s disease in the post-traumatic setting did not appear greater than found in the general population. The clinical spectrum pertaining to recurrent vestibulopathy, Meniere’s disease, delayed endolymphatic hydrops, drop attacks, superior semicircular canal dehiscence syndrome, and uncompensated peripheral vestibular loss are discussed.